Enhanced activation of peroxymonosulfate by a floating FeMo3Ox/C3N4 photocatalyst under visible-light assistance for oxytetracycline degradation: Performance, mechanisms and comparison with H2O2 activation. (1st January 2023) - Liu, Yiyang; Wang, Xuejiang; Sun, Qiunan; Yuan, Meng; Sun, Zhenhua; Chen, Liuyu; Zhang, Yanan; Xia, Siqing; Zhao, Jianfu
Abstract: In this study, a floating FeMo3 Ox /C3 N4 -EP (FM-C-P) composite with highly stability and reusability was synthesized by an impregnation/calcination process and used to activate peroxymonosulfate (PMS) for oxytetracycline (OTC) degradation under visible light irradiation. The results demonstrated that 98.1% of OTC (50 mg/L) removal can be achieved by the activation of PMS (5 mM) using FM-C-P (1 g/L) in 30 min under visible light irradiation. The pseudo-first-order rate constant was calculated to be 0.181 min −1 . The degradation process with PMS was hardly affected by pH (3–11) and co-existing substance. ·SO4 −, ·OH, ·O2 − and 1 O2 were produced in the Vis/PMS/FM-C-P system and 1 O2 was determined to be the main reactive oxygen species (ROSs). The high efficiency of ROSs production mainly contributed to two mechanisms. Firstly, via the combination of ≡Fe (II)-·SO5 − and free state ·SO5 −, 1 O2 could be generated on the Fe-Nx site. Secondly, photo-induced electrons in the FeMo3 Ox /g-C3 N4 heterojunction could react with Fe (III) and Mo (VI) to form catalytically active species Fe (II) and Mo (IV). Moreover, the proposed degradation pathway and the toxicity of intermediated products was analyzed. Overall, this study was expected to deepen the understanding of the photo-assisted PMS activation and the generation of 1 O2 with the presence of metal-oxide/C3 N4 heterojunction. Graphical abstract: Image 1 Highlights: FeMo3 Ox /C3 N4 -EP (FM-C-P) exhibits high reactivity for PMS activation. Vis/PMS/FM-C-P system offers a broader applicability than Vis/H2 O2 /FM-C-P system. ·SO4 − played an important role in the oxytetracycline degradation and TOC remove. Fe-Nx sites could enhance the combination of ·SO5 − to form 1 O2 .